2014
DOI: 10.1074/jbc.m114.565010
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Role of Nucleophosmin Three-helix Bundle and a Flanking Unstructured Tail in the Interaction with G-quadruplex DNA

Abstract: Background: Nucleophosmin is a nucleolar protein that interacts with G-quadruplexes. Results: Site-directed mutagenesis and molecular dynamics unravel the role of single residues in complex formation. Conclusion: A disordered segment of nucleophosmin contributes to G-quadruplex recognition by facilitating the formation of an encounter complex and transiently interacting with the G-quadruplex. Significance: Understanding the role played by flanking fuzziness is an important issue in protein/DNA interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The CTD of NPM1 is an essential element for the activities of this multifunction protein. It is crucial for shuttling and for its interactions with DNA (6, 23, 31), and its functionality relies on the specific fold that it adopts: a 3‐helix bundle. Investigations have indicated that the 3 helical regions of the domain are endowed with a high intrinsic propensity for this structural element (9, 12).…”
Section: Discussionmentioning
confidence: 99%
“…The CTD of NPM1 is an essential element for the activities of this multifunction protein. It is crucial for shuttling and for its interactions with DNA (6, 23, 31), and its functionality relies on the specific fold that it adopts: a 3‐helix bundle. Investigations have indicated that the 3 helical regions of the domain are endowed with a high intrinsic propensity for this structural element (9, 12).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the three-helix bundle engages the G-quadruplex phosphate scaffold with a positively charged groove located between helices H1 and H2 (Figure 1C). Structural studies also revealed that the terminal part of the central domain, which is unstructured and markedly positively charged, is also necessary for high affinity binding, through both long range electrostatic effects and transient interactions with the G-quadruplex [44, 45]. NPM1 loses its nucleolar localization following lysine acetylation played by p300 [46] and, consistently with structural studies, both lysine residues located in the three-helix bundle at the G-quadruplex interface (Lys250, Lys257 and Lys267) [43] and lysine residues located in the flanking unstructured tail (Lys229 and Lys230) are acetylated by p300 [46].…”
Section: Npm1 Structurementioning
confidence: 99%
“…Several investigations pointed out that the CTD of NPM1 is crucial to specifically recognize G-quadruplex DNA motifs [ 74 , 75 , 76 , 77 , 78 , 79 ]. Initial contrasting NMR analyses established that G-quadruplex recognition by NPM1 was primarily due to residues belonging to the helices H1 and H2 of the CTD [ 75 ], but more recently molecular dynamics simulations and SPR data indicated that the unstructured region plays a primary role in the mechanism.…”
Section: Dna Binding Proteinsmentioning
confidence: 99%
“…Initial contrasting NMR analyses established that G-quadruplex recognition by NPM1 was primarily due to residues belonging to the helices H1 and H2 of the CTD [ 75 ], but more recently molecular dynamics simulations and SPR data indicated that the unstructured region plays a primary role in the mechanism. Besides, facilitating the formation of the DNA-complex through long range electrostatic interactions, it directly contacts the G-quadruplex scaffold through multiple and transient electrostatic interactions significantly enlarging the contact surface [ 78 ].…”
Section: Dna Binding Proteinsmentioning
confidence: 99%